Repeated Exposure of Vancomycin to Vancomycin-Susceptible Staphylococcus aureus (VSSA) Parent Emerged VISA and VRSA Strains with Enhanced Virulence Potentials - Nguyen, An; Roy, J. Jean Sophy; Kim, Ji-Hoon; Yun, Kyung-Hee; Lee, Wonsik; Kim, Kyeong Kyu; Kim, Truc; Chaurasia, Akhilesh Kumar (The journal of microbiology, 2024)
The emergence of resistance against the last-resort antibiotic vancomycin in staphylococcal infections is a serious concern for human health. Although various drug-resistant pathogens of diverse genetic backgrounds show higher virulence potential, the underlying mechanism behind this is not yet clear due to variability in their genetic dispositions. In this study, we investigated the correlation between resistance and virulence in adaptively evolved isogenic strains. The vancomycin-susceptible Staphylococcus aureus USA300 was exposed to various concentrations of vancomycin repeatedly as a mimic of the clinical regimen to obtain mutation(s)-accrued-clonally-selected (MACS) strains. The phenotypic analyses followed by expression of the representative genes responsible for virulence and resistance of MACS strains were investigated. MACS strains obtained under 2 and 8 µg/ml vancomycin, named Van2 and Van8, respectively; showed enhanced vancomycin minimal inhibitory concentrations (MIC) to 4 and 16 µg/ml, respectively. The cell adhesion and invasion of MACS strains increased in proportion to their MICs. The correlation between resistance and virulence potential was partially explained by the differential expression of genes known to be involved in both virulence and resistance in MACS strains compared to parent S. aureus USA300. Repeated treatment of vancomycin against vancomycin-susceptible S. aureus (VSSA) leads to the emergence of vancomycin-resistant strains with variable levels of enhanced virulence potentials.